A Novel and Selective Nociceptin Receptor (NOP) Agonist (1‐(1‐((cis)‐4‐isopropylcyclohexyl)piperidin‐4‐yl)‐1H‐indol‐2‐yl)methanol (AT‐312) Decreases Acquisition of Ethanol‐Induced Conditioned Place Preference in Mice. (19th January 2018) - Zaveri, Nurulain T.; Marquez, Paul V.; Meyer, Michael E.; Polgar, Willma E.; Hamid, Abdul; Lutfy, Kabirullah
Abstract : Background: Nociceptin/orphanin FQ, the endogenous peptide agonist for the opioid receptor‐like receptor (also known as NOP or the nociceptin receptor), has been shown to block the acquisition and expression of ethanol (EtOH)‐induced conditioned place preference (CPP). Here, we report the characterization of a novel small‐molecule NOP ligand AT‐312 (1‐(1‐((cis)‐4‐isopropylcyclohexyl)piperidin‐4‐yl)‐1H‐indol‐2‐yl)methanol) in receptor binding and GTP γ S functional assays in vitro. We then investigated the effect of AT‐312 on the rewarding action of EtOH in mice using the CPP paradigm. Further, using mice lacking the NOP receptor and their wild‐type controls, we also examined the involvement of NOP in the effect of AT‐312. Motivational effects of AT‐312 alone were also assessed in the CPP paradigm. Methods: Female mice lacking NOP and/or their wild‐type controls received conditioning in the presence or absence of the NOP agonist [AT‐312 (1, 3, and 10 mg/kg) or the control NOP agonist SCH221510 (10 mg/kg)] followed by saline/EtOH for 3 consecutive days (twice daily) and tested for CPP in a drug‐free state on the next day. Results: Our in vitro data showed that AT‐312 is a high‐affinity, selective NOP full agonist with 17‐fold selectivity over the mu opioid receptor and >200‐fold selectivity over the kappa opioid receptor. The results of our in vivo studies showed that AT‐312 reduced EtOH CPP at the lowest dose (1 mg/kg) tested but completely abolished EtOH CPP at higher doses (3 or 10 mg/kg) compared to their vehicle‐treated control group. AT‐312 (3 mg/kg) did not alter EtOH‐induced CPP in mice lacking NOP, confirming that AT‐312 reduced EtOH CPP through its action at the NOP receptor. AT‐312 (3 mg/kg) did not induce reward or aversion when administered alone, showing that the novel small‐molecule NOP agonist shows efficacy in blocking EtOH‐induced CPP via the NOP receptor. Conclusions: Together, these data suggest that small‐molecule NOP agonists have the potential to reduce alcohol reward and may be promising as medications to treat alcohol addiction.